EFEKTIFITAS MEDIASI DALAM PENYELESAIAN SENGKETA HARTA BERSAMA DI PENGADILAN AGAMA MAKASSAR - Abu Rahman Baba (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
This research study about “Mediation Effectiveness in Dispute Settlement of Property in Religious Courts of Makassar”. The aim of this research is to find out the effectiveness of mediation in the settlement of disputes over property. The other cases, to know the factors that influence the process of mediation in the dispute of property in Religious Courts of Makassar. This research is empirical field research with normative cases. The population of this research are mediators, advocates and seekers of justice at Religious Courts of Makassar. The types and sources of data required in this research are primary and secondary data. Techniques used in order to obtain data are questionnaires, interviews, documentation. Data analysis techniques use qualitative and quantitative analysis. Based on the analysis of the implementation of mediation process in the dispute settlement property Religious Court of Makassar has not been effective. Some Factors affecting the process of mediation in the dispute of property in Religious Court of Makassar are consists of legal substance, legal structure and legal culture.